Savant Syndrome: Realities, Myths and Misconceptions. - Treffert, Darold (Journal of Autism & Developmental Disorders, 2014)
It was 126 years ago that Down first described savant syndrome as a specific condition and 70 years ago that Kanner first described Early Infantile Autism. While as many as one in ten autistic persons have savant abilities, such special skills occur in other CNS conditions as well such that approximately 50 % of cases of savant syndrome have autism as the underlying developmental disability and 50 % are associated with other disabilities. This paper sorts out realities from myths and misconceptions about both savant syndrome and autism spectrum disorders (ASD) that have developed through the years. The reality is that low IQ is not necessarily an accompaniment of savant syndrome; in some cases IQ can be superior. Also, savants can be creative, rather than just duplicative, and the skills increase over time on a continuum from duplication, to improvisation to creation, rather than diminishing or suddenly disappearing. Genius and prodigy exist separate from savant syndrome and not all such highly gifted persons have Asperger's Disorder. This paper also emphasizes the critical importance of separating 'autistic-like' symptoms from ASD especially in children when the savant ability presents as hyperlexia (children who read early) or as Einstein syndrome (children who speak late), or have impaired vision (Blindisms) because prognosis and outcome are very different when that careful distinction is made. In those cases the term 'outgrowing autism' might be mistakenly applied when in fact the child did not have ASD in the first place.